Pengaruh Model Pembelajaran Self Regulated Learning Terhadap Kemampuan Berpikir Kreatif Siswa Kelas V di SDN Tenggilis Mejoyo 1 Surabaya - Melly Nur Eka Anggraini; Bahauddin Azmy; Via Yustitia (Universitas Mathla'ul Anwar Banten, 2022)
Creative thinking skills necessary to develop the human self and solve problems encountered in everyday life. See the results of the study of Trends in International Mathematic and Science Study (TIMSS) that the ability of creative thinking of students in Indonesia tend to be still less. Low creative thinking ability of students can be caused by a learning model that has not been able to increase the creative thinking of the students. Learning model of Self Regulated Learning a model where students are given the flexibility so that the aspect of creative thinking of students who are low can be increased to manage the learning itself. The study aims its to know the influence of learning model of Self-Regulated Learning on the ability of creative thinking of students of class V SDN Tenggilis Mejoyo 1 Surabaya.The population is student of class V of the academic year 2021/2022 SDN Tenggilis Mejoyo 1 Surabaya. The sample was taken by cluster random sampling technique so that the obtained class 5-A (grade control) and 5-B (experimental class). The method used test methods and.The results showed that there is influence of learning model of Self-Regulated Learning on the ability of creative thinking of students. It is shown the average of the experimental class creative thinking skills of students taught through the learning model of Self-Regulated Learning is better than the control class that does not use model pembelajaran Self Regulated Learning.